Investigating predictors of problematic alcohol, cannabis, and nicotine use among legal users of all three substances - Shephard, Aaron; Dölek, Şimal; Barrett, Sean P. (Frontiers in Psychiatry, 2023)
Background The three most used substances—alcohol, cannabis, and nicotine—are frequently concurrently. Use of each substance has been connected to an increased probability of use of the other substances, and the problematic use of each substance has been linked to demographic factors, substance use factors, and personality. However, little is known about which risk factors are most important for consumers of all three substances. This study examined the extent to which various factors are associated with dependence on alcohol, cannabis, and/or nicotine in users of all three substances. Methods 516 Canadian adults with past month use of alcohol, cannabis, and nicotine completed online surveys querying their demographics, personality, substance use history, and levels substance dependence. Hierarchical linear regressions were used to determine which factors best predicted levels of dependence on each substance. Results Alcohol dependence was associated with levels of cannabis and nicotine dependence, and impulsivity, with 44.9% of variance explained. Cannabis dependence was predicted by alcohol and nicotine dependence levels, impulsivity, and the age of onset of cannabis use, with 47.6% of variance explained. Nicotine dependence was best predicted by alcohol and cannabis dependence levels, impulsivity, and dual use of cigarettes and e-cigarettes, with 19.9% of variance explained. Conclusions Alcohol dependence, cannabis dependence, and impulsivity were the strongest predictors for dependence on each of the substances. A strong relationship between alcohol and cannabis dependence was evident, warranting further research.